The unique structure of the highly conserved PPLP region in HIV-1 Vif is critical for the formation of APOBEC3 recognition interfaces - Yasumasa Iwatani; Kazuhiro Matsuoka; Hirotaka Ode; Mai Kubota; Yoshihiro Nakata; Yuka Setoyama; Kanako Kojima; Mayumi Imahashi; Yoshiyuki Yokomaku (mBio)
ABSTRACT The human cellular cytidine deaminases APOBEC3s (A3s) inhibit virion infectivity factor (Vif)-deficient HIV-1 replication. However, virus-encoded Vifs abolish this defense system by specifically recruiting A3s to an E3 ubiquitin ligase complex to induce their degradation. The highly conserved Vif PPLP motif is critical for the Vif-mediated antagonism of A3s and is believed to be important for Vif multimerization. However, how the PPLP motif dictates the functions of Vif remains unclear. Here, we aimed to elucidate this mechanism using biochemical and structural biology approaches. First, we found that no stable Vif multimer complexes formed in our tandem coimmunoprecipitation assays. Next, a series of Vif truncation mutants were constructed, and the short α-helix α6 just downstream of PPLP was found to be the smallest fragment essential for efficient A3G degradation in cells. In silico structural analysis suggested that PPLP-α6 adopts a stable L-shaped conformation when complexed in Vif/CBF-β and contributes to the structural integrity of Vif. In vitro ubiquitination assays with recombinant proteins confirmed that PPLP-α6 is necessary to form the functional complex of the E3 ligase adaptor of Vif/CBF-β/elongin B/elongin C. Additionally, mutations of the highly conserved PPLP-α6 hydrophobic residues severely disrupted Vif function. In the Vif structure, PPLP-α6 is positioned behind α1-α2 that constitutes the A3-binding Vif interfaces. Therefore, both the PPLP motif and α6 play critical allosteric roles in maintaining the integrity of the A3 interaction interfaces. Our findings will also provide important data for the design of novel anti-HIV-1 compounds that disrupt the A3-binding Vif interfaces.IMPORTANCEThe APOBEC3 (A3) family enzymes potently block the replication of retroviruses, such as HIV-1. However, HIV-1 expresses Vif, a small multifaceted protein that binds and specifically eliminates A3s in infected cells via ubiquitination–proteasome degradation. Thus, A3–Vif interactions are attractive targets for anti-HIV-1 drug development. The Vif PPLP motif that is distal from these interfaces is necessary for A3 degradation; however, the mechanism by which PPLP participates in A3 degradation is unknown. In this study, we performed biochemical and structural biology analyses to elucidate the underlying mechanisms involved. We found that the PPLP motif, in addition to the short downstream fragment α6, forms a stable L-shaped conformation and acts as a scaffold for the A3 recognition interfaces. Importantly, mutations in α6 abolished Vif function to antagonize multiple A3 family enzymes. These findings provide important data for the development of novel HIV-1 inhibitors that utilize A3s as cellular defense enzymes.